(untitled) (Contemporary Journal of Social Science Review, 2025)
This study examines the role of community policing practices in fostering public trust in the police using the Sargodha model police station as an example. This study is based on the premise that police effectiveness depends not only on fighting crime but also on public trust and police legitimacy. A quantitative research design was used, and data were collected from a total of 70 respondents, including 45 community residents and 25 police officers, using a structured questionnaire based on a Likert scale format. Data collected from community respondents were used to analyze the relationship between community policing and public trust, and data from police respondents served as the basis for descriptive analysis. Statistical analyzes were performed using the Statistical Package for the Social Sciences (SPSS), and Pearson correlations were used to examine relationships between key variables. The results indicate a significant positive relationship between community policing and public trust in the police. Results show that increased police and community engagement, equity, and accessibility lead to increased levels of public trust. This study contributes to the limited empirical literature on community policing in Pakistan and provides practical ideas for police reform aimed at strengthening police-community relations and improving crime prevention.